Wizerunek e-zinu „Parallax” – charakterystyka, identyfikacja, budowanie marki - Wich-Szymczak, Urszula (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article discusses image development in “Parallax” (an internet magazine devoted to computer games), with a special focus on aspects of visual identification. The article presents the characteristics of “Parallax”, the stages of building its image, and the building of the brand, with special attention paid to issues such as the design of name, logo, typography, and the selection of the appropriate color. The aim of the study is to demonstrate how conscious image building affects perceptions of the e-zine. Thanks to developments in interactivity, the mass media communication model is changing. The engagement of the sender and receiver provides clues for the proper functioning of this new-born journalism type, which is a key contributor that is rapidly gaining importance in relation to traditional media types. The author reveals plans to increase the contribution of graphic, visual aspects in internet media models when comparing them to “paper” media, which often seems to be underestimated by publishers and explains its importance for identity creation in internet media.